2007
DOI: 10.1007/s10827-006-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Local cortical circuit model inferred from power-law distributed neuronal avalanches

Abstract: How cortical neurons process information crucially depends on how their local circuits are organized. Spontaneous synchronous neuronal activity propagating through neocortical slices displays highly diverse, yet repeatable, activity patterns called "neuronal avalanches". They obey power-law distributions of the event sizes and lifetimes, presumably reflecting the structure of local circuits developed in slice cultures. However, the explicit network structure underlying the power-law statistics remains unclear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 48 publications
1
44
1
Order By: Relevance
“…Indeed, the finding of scale invariance does not exclude long-range or short-range heterogeneous corticocortical projections. Numerical simulations have shown that neuronal avalanches can arise at the critical state in models with scale-free (26), fully connected (27), random (28), and nearest-neighbor (18,26) topologies, although in each case the conditions to reach criticality can be different. In cortical cultures, the neuronal avalanches establish a functional small-world architecture with specific and highly diverse point-topoint connectivity between cortical sites that is, the network representing these site activations is densely interconnected, globally as well as locally (29).…”
Section: Scale Invariance In Time Nlfp Amplitude and Finite-size Scmentioning
confidence: 99%
“…Indeed, the finding of scale invariance does not exclude long-range or short-range heterogeneous corticocortical projections. Numerical simulations have shown that neuronal avalanches can arise at the critical state in models with scale-free (26), fully connected (27), random (28), and nearest-neighbor (18,26) topologies, although in each case the conditions to reach criticality can be different. In cortical cultures, the neuronal avalanches establish a functional small-world architecture with specific and highly diverse point-topoint connectivity between cortical sites that is, the network representing these site activations is densely interconnected, globally as well as locally (29).…”
Section: Scale Invariance In Time Nlfp Amplitude and Finite-size Scmentioning
confidence: 99%
“…Although not identical to the critical point of phase transitions, because it lacks the property of universality, the critical point of neural systems has attracted increasing theoretical and computational interest because of its importance to neural systems function [21,[30][31][32][33][34][35][36][37][38][39][40]. A critical neural system is balanced between a phase where activity is damped and a phase where activity is expanding.…”
Section: The Critical Pointmentioning
confidence: 99%
“…Avalanche-like behavior occurs in wide-ranging examples in nature, from sand piles (13) and magnetic turbulence in plasmas (14) to solar flares (15), earthquakes (16), and neuronal activity (17), and has even been described in microtubule dynamics (18) and neuronal growth cone motility (19). Avalanching systems share the common feature that they are driven toward an unstable state by an input of energy or material that accumulates until an avalanche returns the system to a more stable state.…”
mentioning
confidence: 99%